Can the gold standard be beaten? How reliable are various modifications of the Synacthen test compared to the insulin tolerance test - Kosak, M; Duskova, M; Starka, L; Jandikova, H; Pospisilova, H; Sramkova, M; Hana, V; Krsek, M; Springer, D; Simunkova, K (Physiological research, 2017)
Criteria for the evaluation of the insulin tolerance test (ITT) and Synacthen test are still a matter of debate. The objective of the study was to make a comparison of serum and salivary cortisol during four stimulation tests. Sixty four healthy volunteers underwent the ITT, the Synacthen test with 1 (LDST), 10 (MDST) and 250 (HDST) microg dose of ACTH. Maximum serum cortisol response was observed at the 90 min of the ITT (49 %), HDST (89 %) and MDST (56 %) and at the 40 min of the LDST (44 %). Results expressed as 95 % confidence intervals: 408.0-843.6 and 289.5-868.1 nmol/l in the IIT at 60 and 90 min. In the HDST and the MDST serum cortisol reached the maximum at 90 min 542.6-1245.5 and 444.2-871.3 nmol/l. Levels of salivary cortisol followed the same pattern as serum cortisol. Salivary cortisol reached the maximum response in the HDST and the MDST at 90 min and at 40 min in the LDST. We confirmed good reliability of all tests with respect to timing of response and maximum response compared to the ITT. We proved that the MDST test can provide the similar response in serum cortisol to the HDST. Measuring either salivary cortisol or ACTH levels did not provide any additional benefit then measuring serum cortisol by itself.
Keywords: reprodukovatelnost výsledků; mužské pohlaví; Male; Insulin Resistance; Humans; Female; Reproducibility of Results; hydrokortison; referenční standardy; lidé; Cosyntropin; Hypothalamo-Hypophyseal System; ženské pohlaví; Insulin; Reference Standards; systém hypofýza - nadledviny; inzulinová rezistence; Pituitary-Adrenal System; kosyntropin; inzulin; systém hypotalamus-hypofýza; dospělí; Adult; Saliva; sliny; Hydrocortisone